Der 'Gefährder' und das 'Gefährdungsrecht' eine rechtssoziologische Analyse am Beispiel der Urteile des Bundesverfassungsgerichts über die nachträgliche Sicherungsverwahrung und die akustische Wohnraumüberwachung - Böhm, María Laura (Universitätsverlag Göttingen, 2011)
Endanger law ('Gefährdungsrecht') is a criminal law which is seeking security - and thereafter fighting 'risks' and 'dangers' - as its main objective and which is acting on the basis of risk patterns developed by this law itself. Individuals who fit these characteristics are being fought against as endangerers, that means, as high risky figures - and not as offenders. In this work it is presented this figure which has been constructed by the criminal policies and system in Germany during recent years, and has been co-constructed by the Constitutional Court in at least two cases: in the case of the acoustic home surveillance and in the case of the subsequent incapacitation order. Here is (critically) explained the internal logic and rationality which is leading this endanger law.